2009
DOI: 10.5424/sjar/2009074-1112
|View full text |Cite
|
Sign up to set email alerts
|

Short communication. Response of chickpea (Cicer arietinum L.) to soil zinc application

Abstract: The response of chickpea (Cicer arietinum) to Zn nutrition was studied in pot experiments under natural conditions using four acid soils of northwest Spain during 2007 and 2008. Five concentrations of Zn (0, 1, 2, 4 and 8 mg Zn/pot) were added to the pots as Zn chelate. Chickpea responded to the soil Zn applications and there were highly significant differences between soils. At maturity plants fertilized with Zn had greater total dry matter production mainly due to increments in pods weight. The lowest yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In a previous Zn fertilization study involving pots Khan (1998) also reported an increase in grain yield, which was mainly due to an increase in the number of pods per plant, with the application of Zn when the soil had high moisture availability. Valenciano et al (2009) also obtained similar results using the same types of soils but with different environmental conditions. The analysis of the variance established that the environment × Zn interaction only had a low significant effect on the number of seed per pod and on the 1,000-seed weight, but there was no significant difference on yield.…”
Section: Discussionsupporting
confidence: 72%
“…In a previous Zn fertilization study involving pots Khan (1998) also reported an increase in grain yield, which was mainly due to an increase in the number of pods per plant, with the application of Zn when the soil had high moisture availability. Valenciano et al (2009) also obtained similar results using the same types of soils but with different environmental conditions. The analysis of the variance established that the environment × Zn interaction only had a low significant effect on the number of seed per pod and on the 1,000-seed weight, but there was no significant difference on yield.…”
Section: Discussionsupporting
confidence: 72%
“…Valenciano et al (2009;2010) obtained similar results in the same environments but under pot conditions at high moisture availability; they also recorded differences for 1000-seed weight. Zn soil application increased yield (Khan et al 2000) and, as with the common bean (Valenciano et al 2007), this increase was the result of an increase in the number of pods per plant (Khan 1998;Valenciano et al 2009;2010). Although the response to Zn soil application varied with environment, as Loneragan & Webb (1993) observed, variance analysis established that the environment)Zn interaction produced no significant differences in growth and yield.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, the highest yield was also obtained with treatment at 4 WAE. Yield was increased due to greater pods plant -1 number, this yield component being closely related to final seed yield (Maiti and WescheEbeling, 2001;Valenciano et al, 2009). Mo application after emergence improved yield until 4 WAE.…”
Section: Discussionmentioning
confidence: 99%